(3cJGH aj GdJhMjOs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf Ydeg GdHjGf hUdGJg Ydi SjOfG eMeO GdeHYhK HGdaQbGf aGQbkG Hjf GdHQgGf hGdHgJGf s
(3BNQgG (B:s
(3hGdCUd Cf fSCd Gddg YR hLd GdYUeI ef GdaJfI hGdSdGeI ef GdeMfI hdG Mhd hdGbhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLejYf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3fbdJ ef fSNI HNW GdYdGeI TjN GdESdGe GdYHGOi QMeg Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(585) s
Keywords: (3GdJhMjO hGdedd hGdfMds